Subalternity and Memory in El hombre de chocolate by Quince Duncan - Wintter Vargas, Raquel Victoria (2025)
This essay explores the representation of subalternity in three stories from the book El hombre de chocolate (The Chocolate Man) by Quince Duncan (2023), whose main character is Marcus Garvey. The fictionalization of this activist is analyzed to preserve the historical and cultural memory of the African and Afrodescendant people in Costa Rica. Furthermore, it is found that the three literary works highlight the hegemonic/subaltern relations between the White population and Black people, as the Afro-Caribbean people depicted in the texts are victims of discrimination, exploitation, and questioning of their cultural practices